Ecological and historical legacies on global diversity gradients in marine elapid snakes. (3rd December 2020) - Martinez, Pablo A.; F. Gouveia, Sidney; dos Santos, Luiza M.; Carvalho, Fernando H. A.; Olalla‐Tárraga, Miguel Á.
Abstract: Global diversity gradients have been extensively investigated for several biological groups. However, little is known whether the diversity drivers of clades that underwent major environmental transition (e.g., from land to sea) are equivalent across these different environmental settings. Here, we ask if the pattern of diversity of marine elapid snakes is determined by factors analogous to those previously found for terrestrial lineages. Through a model selection framework, we compare the effect of factors that represent five ecological and historical hypotheses. We found that both ecological and historical factors play significant roles, but habitat structure, which can be linked to historical climatic changes, was better supported. This result agrees with that previously found for terrestrial elapids, despite the different environmental pressures in terrestrial and marine contexts. Our findings suggest an equivalence of the underlying process of diversity gradient within the same lineage from land and sea, irrespective of the different physiological, spatial and historical constraints.